Raw Materials for Paper - Guha, S. R. D. (Indian Forester, 1975)
The article gives a brief description of paper making and the statistics of paper production. The essential factors to be considered for selecting a fibrous raw material for paper making are discussed. A detailed description follows of the following indigenous raw materials tested for paper making by the Forest Research Institute and being used at present by the Indian Paper Industry - Soft woods, Grasses, Bamboo, Straws, Bagasse and Hardwoods.